Carbon Emission Disclosure, ESG, Assets Growth on Financial Performance: The Moderating Role of Firm Size - Vanica Eprillia Kuswoyo; Abdul Mukti Soma (International Journal of Applied Management and Business, 2026)
Purpose – The objective of this study is to analyze the effect of CED, ESG and AG on company financial performance, measured by Tobin’s Q and ROA, while evaluating the moderating role of company Size across energy businesses in the ASEAN-5 countries. Methodology/approach – The study uses a quantitative causal research design with panel data regression analysis. The sample comprises 141 firm-year observations, from 47 publicly listed energy businesses in Indonesia, Malaysia, Singapore, Thailand and the Philippines throughout the period 2022-2024. Secondary data were acquired from annual reports, sustainability reports and Refinitiv Eikon database. The postulated ideas were tested using REM and MRA. Findings – Both CED and AG yield a highly positive effect regarding Tobin’s Q alongside ROA, according to the empirical data. Conversely, ESG shows an absence of significant consequences for either indicator of firm financial performance. Furthermore, Firm Size operates as an essential moderating element concerning the links uniting CED with Tobin’s Q as well as ESG with Tobin’s Q, whereas it alters neither the connection binding AG to Tobin’s Q nor any interplay linking the independent variables with ROA. Novelty/value – Insights from this research design enrich the existing sustainability and corporate finance literature by jointly evaluating CED, ESG, AG, and the moderating effect of Firm Size across market-based and accounting-based financial performance dimensions within a cross-country ASEAN-5 energy sector environment. These conclusions supply actionable guidance for investors, managers, and policy authorities regarding the value of clear environmental disclosure alongside sustainable asset management intended for advancing firm financial performance.